KAJIAN VIKTIMOLOGI TERHADAP KORBAN PENIPUAN PENDAFTARAN CALON PEGAWAI NEGERI SIPIL (CPNS) DI WILAYAH KEPOLISIAN DAERAH NUSA TENGGARA TIMUR - Ndolu, Indiani Cristina; Fallo, Debi F. Ng; Manuain, Orpa Ganefo (Petitum Law Journal, 2024)
: This study examines the phenomenon of fraud that occurs in the registration of Civil Servant Candidates (CPNS) in the East Nusa Tenggara Regional Police (Polda NTT) from a victimology perspective.The main points in this problem are (1) What is the role of victims in the occurrence of fraudulent crimes in the recruitment of prospective civil servants in the East Nusa Tenggara Region? (2) What are the legal protection efforts for victims of fraud in the recruitment of civil servant candidates? The purpose of this study is to understand the role of victims in the occurrence of CPNS fraud and the legal protection efforts that can be provided to victims. This study uses an empirical legal approach, with data collection through interviews and literature studies. The analysis was carried out descriptively qualitatively to describe the impact experienced by victims and the factors that make them vulnerable to fraud. The results of the study show that (1) victims have an active role in the occurrence of this crime, including due to excessive trust in the perpetrators, ignorance of official procedures, and social and economic pressures that encourage them to take risks. (2) From the aspect of legal protection, victims have the right to restitution, legal assistance, and protection from the police.